Epithelial Abnormalities in the Small Intestine of Zambian Children With Stunting - Mulenga, Chola; Sviben, Sanja; Chandwe, Kanta; Amadi, Beatrice; Kayamba, Violet; Fitzpatrick, James A. J.; Mudenda, Victor; Kelly, Paul (Frontiers in Medicine, 2022)
Background Environmental enteropathy (EE) contributes to impaired linear growth (stunting), in millions of children worldwide. We have previously reported that confocal laser endomicroscopy (CLE) shows fluorescein leaking from blood to gut lumen in vivo in adults with EE. We set out to identify epithelial lesions which might explain this phenomenon in Zambian children with stunting non-responsive to nutritional support. Methods We performed confocal laser endomicroscopy (CLE) in 75 children and collected intestinal biopsies for histology in 91 children. CLE videos were evaluated, employing the Watson score to determine severity of leakiness. Morphometry was carried out on well-orientated mucosa and 3 biopsies were examined on electron microscopy. Results CLE demonstrated substantial leakage from circulation to gut lumen in 73 (97%) children. Histology consistently showed characteristic changes of EE: villus blunting, lamina propria and epithelial inflammation, and depletion of secretory cells (Paneth cells and goblet cells). Epithelial abnormalities included marked variability in epithelial height, disorganised and shortened microvilli, dilated intercellular spaces, pseudostratification, formation of synechiae between epithelium on adjacent villi, crypt destruction, and abundant destructive lesions which may correspond to the microerosions identified on CLE. Conclusions Epithelial abnormalities were almost universal in Zambian children with non-responsive stunting, including epithelial microerosions, cell-cell adhesion anomalies, and defects in secretory cells which may all contribute to impairment of mucosal barrier function and microbial translocation.